Increasing production capacity through diversification of mangrove processing - Yuli Budiati; Dewi Larasati; Amerti Irvin Widowati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The Mina Karya Fishery Product Marketers Processing Group (Poklahsar) is a business group in Tambaklorok, Semarang, that processes marine products. It currently faces limitations in product processing and diversification, marketing, and finance. This group has the potential to grow and reach a broader market. PKM activities aim to increase POKLAHSAR 'Mina Karya' capacity to diversify processed mangroves and optimize marketing and financial management capabilities. Activity methods include training, assistance in using appropriate technology related to mangrove-processed diversification, and finance and marketing management skills. The results of PKM activities are an increase in the capacity of Poklahsar Mina Karya in diversifying processed mangrove production and the ability of the results of PKM activities to increase the capacity of Poklahsar Mina Karya in production, marketing, and finance. Spinner machine assistance accelerates the draining process to only 10 minutes and durability for three months. The disc mill flouring machine technology helped diversify products and increase Marketing and finance training, helped partners expand market reach to a national scale, and optimized business management, creating new economic opportunities.